Predictors of Pacing-Induced Cardiomyopathy in Patients with Permanent Right Ventricular Pacing and Preserved Left Ventricular Systolic Function - Perepeka, Eugene O.; Trembovetska, Olena M.; Kravchuk, Borys B.; Nastenko, Ievgen A.; Sychyk, Maryna M. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Right ventricular pacing may impair left ventricular systolic function in patients with reduced left ventricular ejection fraction (LVEF). The aim. To determine the frequency of pacing-induced cardiomyopathy (PICM) in patients with permanent right ventricular pacing (at least 90%) and preserved LVEF (≥50%). To determine the risk factors for the occurrence of PICM. Materials and methods. The study included 34 patients with indications for permanent ventricular pacing in whom pacemaker was implanted from 2012 to 2022 (mean follow-up period 44.97 ± 28.45 months). PICM was defined as a decrease in LVEF <45% during follow-up regardless of clinical manifestations. Risk factors for PICM were determined through univariate and multivariate regression analysis. Results. The incidence of PICM in this study was 26% during the mean observation period of 44.9 ± 28.4 months. The mean time to the onset of PICM was 29 months in 5 out of 9 patients (55%), the time from implantation to diagnosis of PICM was less than a year. The mean LVEF and end-diastolic volume index at the time of follow-up differed significantly in the groups with and without PICM: 38.6 ± 5.9% vs. 53.5 ± 5.7% (p<0.001) and 97.9 ± 20.75 ml/m2 vs. 60.9 ± 19.32 ml/m2 (p<0.001), respectively. In the PICM group intraventricular asynchrony was 261.1 ± 61 ms vs. 146.1 ± 62.8 ms (p<0.001), interventricular asynchrony 91 ± 36.4 ms vs. 54.2 ± 22.2 ms (p = 0.014), the number of segments with reduced deformation 8.1 ± 2.6 vs. 3.91 ± 2.3 (p<0.001), global longitudinal strain –9.7 ± 2.6 % vs. –14.9 ± 3.4 % (p<0.001). At the time of the follow-up examination, the signal of sensitivity on ventricular lead in the PICM group was significantly reduced compared to patients without PICM (6.26 ± 4.02 mV vs. 11.56 ± 3.86 mV, p = 0.045). Paced QRS width in the PICM group was significantly larger (163 ± 22.7 ms vs. 150.8 ± 14.5 ms) and there were more patients with rate-adapted cardiac pacing in the PICM group: 4 (40%) vs. 2 (8%) (p = 0.0428). In multivariate regression analysis, a wider paced QRS (hazard ratio 1.09 for every 1 ms increment in QRS width, 95% confidence interval 1.01-1.17, p = 0.025) was an independent predictor of PICM. In two patients from PICM group, upgrade of pacemaker system to biventricular pacing was performed with an improvement in the left ventricular contractility: in one patient from 37% to 44%, in another from 34% to 51% in one and two month, respectively. Conclusions. Cardiomyopathy due to right ventricular pacing tends to occur instantaneously in the first years after pacemaker implantation, rather than slowly progressing over time. A wider paced QRS complex is an independent predictor of PICM. Biventricular pacing effectively eliminates the consequences of non-physiological right ventricular pacing, improves left ventricular systolic function.